Celecoxib treatment does not alter recruitment and activation of osteoclasts in the initial phase of experimental tooth movement - Carvalho-Filho, E. P.; Stabile, A. C.; Ervolino, Edilson [UNESP]; Stuani, M. B. S.; Iyomasa, M. M.; Rocha, M. J. A. (Pagepress Publ, 2012)
In a previous study, we reported that the short-term treatment with celecoxib, a nonsteroidal anti-inflammatory drug (NSAID) attenuates the activation of brain structures related to nociception and does not interfere with orthodontic incisor separation in rats. The conclusion was that celecoxib could possibly be prescribed for pain in orthodontic patients. However, we did not analyze the effects of this drug in periodontium. The aim of this follow-up study was to analyze effects of celecoxib treatment on recruitment and activation of osteoclasts and alveolar bone resorption after inserting an activated orthodontic appliance between the incisors in our rat model. Twenty rats (400420 g) were pretreated through oral gavage with celecoxib (50 mg/kg) or vehicle (carboxymethylcellulose 0.4%). After 30 min, they received an activated (30 g) orthodontic appliance, set not to cause any palate disjunction. In sham animals, the appliance was immediately removed after introduction. All animals received ground food and, every 12 h, celecoxib or vehicle. After 48 h, they were anesthetized and transcardiacally perfused through the aorta with 4% formaldehyde. Subsequently, maxillae were removed, post-fixed and processed for histomorphometry or immunohistochemical analyses. As expected, incisor distalization induced an inflammatory response with certain histological changes, including an increase in the number of active osteoclasts at the compression side in group treated with vehicle (appliance: 32.2 +/- 2.49 vs sham: 4.8 +/- 1.79, P<0.05) and celecoxib (appliance: 31.0 +/- 1.45 vs sham: 4.6 +/- 1.82, P<0.05). The treatment with celecoxib did not modify substantially the histological alterations and the number of active osteoclasts after activation of orthodontic appliance. Moreover, we did not see any difference between the groups with respect to percentage of bone resorption area. Taken together with our previous results we conclude that short-term treatment with celecoxib can indeed be a therapeutic alternative for pain relieve during orthodontic procedures.
Keywords: orthodontic treatment; analgesic; inflammation; bone resorption; osteoclasts